Integrating the light and dark sides of student engagement using person-oriented and situation-specific approaches. (June 2016) - Salmela-Aro, Katariina; Moeller, Julia; Schneider, Barbara; Spicer, Justina; Lavonen, Jari
Abstract: This study contributes to the research on student engagement in three ways: 1) by combining questionnaire and situational measures of engagement using the Experience Sampling Method (ESM), 2) by applying a demands-resources model to describe the positive and negative aspects of student engagement, and 3) by adopting a person-oriented approach to describe subgroups of students with different profiles of engagement and burnout symptoms. Two studies were conducted: sample one comprised 255 US high school students (45.5% female, 9th – 12th grade), and sample two 188 Finnish comprehensive and high school students (59.6% female, 9th to 10th grade). Latent profile analyses (LPA) of person-level measures of schoolwork engagement and burnout in the US and Finland revealed four profiles: 1) engaged, 2) engaged-exhausted, 3) moderately burned out (risk for burnout) and 4) burned out. These four groups were identified in both samples, but differed in their prevalence. The groups differed in their state experiences of situational demands, resources and engagement at school. Engagement is not wholly an experience of 'flourishing': some students experienced elevated levels of both engagement and burnout. Thus, positive and negative aspects of engagement should be studied and modeled together. Highlights: 4 profiles identified: engaged, burnout, moderate burnout and engaged-exhausted. Profiles differed in state experiences of situational school demands, resources and engagement. Engagement is not always a flourishing experience, but for some students a rather exhaustive. Positive and negative aspects of engagement should be studied and modeled together.